Deploying unqualified personnel in health records practice: Role substitution or quackery? Implications for health services delivery in Nigeria. Issue 3 (September 2019) - Adeleke, Ibrahim Taiwo; Suleiman-Abdul, Qudrotullaah Bolanle; Aliyu, Amina; Ishaq, Ismaeel A; Adio, Razzaq A
Healthcare professionals are obliged to work collaboratively regardless of their professional differences in order to provide the highest possible standard of care to patients. However, this type of collaboration can also lead to role substitution and, in effect, engagement of unqualified personnel in all health professions, including the health information management profession. This is a particular problem in developing nations such as Nigeria, where this trend has the potential to undermine the delivery of health services, the quality and the confidentiality of health information and trust between patients and healthcare professionals. To clarify and protect the professional identity of qualified health information management professionals in Nigeria and to prevent other experts who also work in health facilities (e.g. IT specialists, librarians) from claiming membership of the profession, the nomenclature for the health information management profession has been changed to health records and information management profession .